2007
DOI: 10.1021/ja0679634
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin Phosphate Synthase:  The Rate of Pyrimidine Carbocation Formation

Abstract: Carbocations have fascinated organic chemists for almost a century, and the properties of this reactive intermediate have been thoroughly studied. 1 Carbocations have been proposed as intermediates in several enzyme-catalyzed reactions, such as the prenyl transfer and cyclization reactions involved in terpene biosynthesis, 2,3 the pyrrole tetramerization involved in porphyrin biosynthesis, 4 the glycosyl transfer reactions involved in a wide variety of glycosylations, 5 and, the topic of this communication, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…In the ligand-bound structure (‘ON’ state, right), a distinct P1 stem and a P2 stem (partial formation of the terminator) are expected to form, thereby blocking formation of the complete terminator stem and leading to transcription read-through. ( B ) Pathway for the enzymatic pyrophosphorylation of HMP using 4-amino-5-hydroxymethyl-2-methylpyrimidine phosphate kinase (ThiD), carried out as previously described (Hanes et al, 2007). ( C ) Plots of the mass-to-charge ratios (m/z) of HMP and HMP-PP prepared by enzymatic pyrophosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ligand-bound structure (‘ON’ state, right), a distinct P1 stem and a P2 stem (partial formation of the terminator) are expected to form, thereby blocking formation of the complete terminator stem and leading to transcription read-through. ( B ) Pathway for the enzymatic pyrophosphorylation of HMP using 4-amino-5-hydroxymethyl-2-methylpyrimidine phosphate kinase (ThiD), carried out as previously described (Hanes et al, 2007). ( C ) Plots of the mass-to-charge ratios (m/z) of HMP and HMP-PP prepared by enzymatic pyrophosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, our use of such transcription assays was made more difficult, because HMP-PP is not commercially available and is known to be relatively unstable (Hanes et al, 2007). Therefore, we freshly generated HMP-PP from HMP and ATP enzymatically (Figure 3B) by using recombinantly produced ThiD protein.…”
Section: Resultsmentioning
confidence: 99%
“…10,17,18 The substrate tolerance of this enzyme now becomes important in the context of TenI function. In the reconstitution of the thiazole biosynthesis described in Figure 2, cThz*-P 14 , the product of the thiazole synthase 6 is clearly a substrate for thiamin phosphate synthase.…”
Section: Resultsmentioning
confidence: 99%
“…The results of extensive labeling studies revealing the origins of the HMP-P atoms are shown in Fig. 12 (26, 27, 28, 29, 30, 31). …”
Section: Enzymes Involved In Pyrimidine Biosynthesismentioning
confidence: 99%